Translating the Divina Commedia for the Chinese Reading Public in the Twenty-First Century - Wong, Laurence (TTR, 2008)
AbstractThis article examines five Chinese translations of Dante’s Divina Commedia, the latest version by the author of this article, which was published in 2003. After making some general observations, the article goes on to discuss translation problems relating to medium, rhythm, metre, rhyme, etc. with reference to Chinese and English versions of Dante’s masterpiece. By substantiating its argument with plenty of examples as well as with a comprehensive survey of the prosodic characteristics of the Chinese and European languages, it establishes criteria by which translations of the Divina Commedia should be judged.